Remote Monitoring of Coupled Tank Accompanied by PLC-OPC-MATLAB Architecture - Bhaskarwar, T. (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper focuses on one of the important aspects in the industry 4.0 revolution which is remote monitoring of industrial process through the Industrial Internet of Things (IIoT). In this paper, the cascade control application of coupled level process plant is considered for remote monitoring with IIoT concept. The level of the tank was regulated using PLC-OPC-MATLAB configuration. In order to control the level of a Coupled tank process, two controllers for primary and secondary loops are used to achieve the desired set point. Proportional Integral Derivative-Proportional (PID-P) control strategy is implemented in primary and secondary loop respectively for tracking the set point with minimum settling time. The ThingSpeak platform, a cloud-based server is used for remote monitoring purpose. Finally, the results of the level response and its online observation shown in the result section. Â© 2019 IEEE.